Operadores de justicia y su responsabilidad penal en los delitos de comisión por omisión. - Andrade Macías, Amado Javier (2013)
The legal research project I have at hand entitled "OPERATORS OF JUSTICE AND CRIMINAL LIABILITY CRIMES COMMISSION IN DEFAULT", which deepened the consequences that fall on our Ecuadorian society, by the parties to the proceedings called and that do not fulfill their roles as guarantors in criminal proceedings: The problem refers to the fact we mark the present investigation. The Theoretical Framework compiles legal doctrine, dogmatic criminal law, domestic law, comparative law and jurisprudence facts. The methodology includes the methods used to determine the degree of effectiveness of the investigation, and on the basis of population and sample, technical and research instruments, data processing techniques to obtain results. The analysis and interpretation of results includes the results of surveys of lawyers in the free exercise of the profession and interviews with judges and prosecutors of Quevedo Canton. The verification of the hypothesis is a reflection of the methodology and analysis and interpretation of the results obtained. The conclusions and recommendations are the result of thorough analysis of the problems and solutions to the problem and hypothesis. The proposal is reflected in the solution to be implemented after extensive study and other research project guidelines.